Rozproszony ekspert a rozproszona baza danych – blogi sceptyczne, naukowe a struktury wiedzy - Nowak, Andrzej (Człowiek i Społeczeństwo, 2013)
The text analyzed a group of blogs. They are considered as an example of a distributed expert and a distributed database. In addition, they illustrate a well-functioning informal collective of producing knowledge. The text indicates the specific functioning of the debate around science and socioscientific controversies in Internet based public sphere. The functioning of grassroots experts and distributed databases should be considered as a reference in an effort the reform of official university based structures of knowledge. Crucial question is how to reconcile the dynamics of the activity created by the blogging platform of reliability achieved in the context of traditional knowledge structures.